Preparation method of cylindrical non-winding battery cell
The positive electrode slurry is prepared by ball milling and pressed into a cylindrical positive electrode. Combined with the separator and negative electrode material, the limitations of traditional winding batteries in terms of energy density, safety and heat dissipation performance are solved, and more efficient space utilization and more stable battery performance are achieved.
Patent Information
- Application Number
- CN202411940066.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-04-01
AI Technical Summary
Traditional winding micro batteries have limitations in terms of energy density, safety and cycle life, especially in terms of volume utilization efficiency, internal stress distribution, heat dissipation performance, and pole sheet inhomogeneity and burrs during manufacturing.
The positive electrode slurry is prepared by ball milling method, and the cylindrical positive electrode is pressed into a cylindrical positive electrode through a cylindrical mold, and then the diaphragm material and the negative electrode material are wrapped to form a cylindrical non-winding battery cell.
It improves the energy density of the battery, reduces the uneven distribution of internal stress, enhances the safety and heat dissipation efficiency of the battery, and reduces the risk of pole fragment fracture and material drop.
Smart Images

Figure CN119742386A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of batteries, and in particular to a method for preparing a cylindrical non-winding battery core. Background Art
[0002] With the rapid development of science and technology, the demand for miniature electronic devices is growing, especially in the fields of wearable devices, smart watches, health monitoring devices, micro medical devices, and IoT sensors. These devices require batteries to be not only small in size, but also have high energy density, high power density, long cycle life, and high safety. Although traditional micro battery technologies, such as button batteries and thin film batteries, meet these requirements to a certain extent, they still have some limitations, especially in terms of energy density and safety.
[0003] Traditional micro batteries, especially button batteries, usually adopt a winding structure, which has certain advantages in manufacturing process, cost control and market application. However, with the continuous growth of application demand, the requirements for battery performance are also increasing. There are some inherent limitations of wound batteries in terms of energy density, safety and cycle life. First, the volume utilization efficiency of wound batteries is relatively low. Due to the limitation of the winding structure, there are certain gaps inside the battery, which limits the energy density of the battery. In addition, during the charging and discharging process of the wound battery, due to the volume expansion and contraction of the positive and negative electrode materials, it is easy to cause uneven distribution of internal stress, thereby affecting the cycle stability and safety of the battery. Secondly, the heat dissipation performance of the wound battery is relatively poor. During high-power discharge or fast charging, a large amount of heat will be generated inside the battery, and the winding structure is not conducive to the rapid diffusion of heat, which is easy to cause the battery temperature to rise, affecting the battery performance and life, and even causing safety problems. Finally, during the manufacturing process of the wound battery, due to the winding and cutting of the material, the unevenness of the pole piece and the generation of burrs may occur, which not only affects the consistency of the battery, but also may cause internal short circuits and increase safety risks. Summary of the invention
[0004] In view of the above problems, the purpose of the present invention is to provide a method for preparing a cylindrical non-wound battery cell. In order to achieve the above purpose, the technical solution adopted by the present invention is: the current collector is embedded in the positive electrode slurry, and then poured into a cylindrical mold for pressing to form a cylindrical positive electrode. Subsequently, the diaphragm material and the negative electrode material are tightly wrapped on the surface of the cylindrical positive electrode in turn, and finally a cylindrical non-wound battery cell is formed.
[0005] In a first aspect, the present invention aims to provide a method for preparing a cylindrical non-wound battery cell, which is specifically prepared by the following steps:
[0006] Step 1: Place the carbon fluoride raw materials with different fluorine-carbon ratios, the conductive agent and the binder in a ball mill in a certain proportion, then inject an appropriate amount of solvent into the ball mill, and then place the corresponding ball mill beads according to a certain ball-to-material ratio, and ball mill at a certain speed for a period of time to obtain the battery positive electrode slurry.
[0007] Step 2: Inject the positive electrode slurry obtained in step 1 into a polytetrafluoroethylene mold with a certain pore size, then embed the rectangular current collector into the positive electrode slurry, let it stand at room temperature for a period of time, then transfer it to a vacuum oven, heat it at a set temperature for a period of time until the solvent is completely evaporated, and finally obtain a cylindrical positive electrode.
[0008] Step 3: Wrap the separator material and the negative electrode lithium ribbon in sequence on the surface of the cylindrical positive electrode obtained in step 2 to form a cylindrical non-wound battery cell.
[0009] The present invention prepares the positive electrode slurry by ball milling and presses it into a cylindrical non-wound battery cell, which is easy to manipulate and convenient for large-scale preparation. In addition, the cylindrical non-wound battery cell prepared by the present invention does not have the C angle in the wound battery cell, which makes it possible to more effectively utilize space and improve the energy density of the battery cell under the same volume of battery cell design. In particular, the structure of the cylindrical non-wound battery cell prepared by the present invention helps to reduce the uneven distribution of internal stress, reduce the risk of pole piece breakage and material drop, and thus improve the safety of the battery.
[0010] Preferably, the fluorine-carbon ratio of the fluorinated carbon material selected in step 1 is 0.5-1.3, for example, it can be 0.5, 0.6, 0.8, 1.0, 1.1 or 1.3, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0011] Preferably, the fluorinated carbon selected in step one includes any one of fluorinated hard carbon, fluorinated graphite, fluorinated graphene, fluorinated carbon nanotubes, fluorinated carbon fibers, fluorinated carbon quantum dots, fluorinated redox graphene, fluorinated carbon microspheres, and fluorinated asphalt, or a combination of at least two of them, preferably fluorinated graphene.
[0012] Preferably, the conductive agent selected in step 1 includes any one of Ketjen black, acetylene black, graphite, activated carbon, carbon nanotubes, and SuperP, or a combination of at least two thereof, preferably Ketjen black.
[0013] Preferably, the binder selected in step 1 includes any one of polyvinylidene fluoride, sodium carboxymethyl cellulose, styrene-butadiene rubber, polytetrafluoroethylene, polyacrylic acid, and polyvinyl alcohol, or a combination of at least two thereof, preferably polyvinylidene fluoride.
[0014] Preferably, the ratio of the fluorinated carbon material to the conductive agent and the binder selected in step 1 can be 95:3:2, 90:5:5, 80:10:10 or 75:15:10, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0015] Preferably, the solvent selected in step 1 can be any one of water, ethanol, methanol, isopropanol, N,N-dimethylformamide, acetonitrile, dimethyl sulfoxide or N-methylpyrrolidone, or a combination of at least two thereof, preferably N-methylpyrrolidone.
[0016] Preferably, the amount of solvent selected in step 1 is 50-300 μL, for example, 50 μL, 100 μL, 150 μL, 200 μL, 250 μL or 300 μL, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0017] Preferably, the ball-to-material ratio selected in step 1 is 6-20, for example, 6:1, 8:1, 12:1, 16:1, or 20:1, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0018] Preferably, the ball milling speed selected in step 1 is 300-1200 r / min, for example, it can be 300 r / min, 500 r / min, 800 r / min, 1000 r / min or 1200 r / min, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0019] Preferably, the ball milling time selected in step 1 is 2-12 h, for example, 2 h, 4 h, 6 h, 8 h, 10 h or 12 h, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0020] Preferably, the aperture size of the polytetrafluoroethylene mold selected in step 2 is 3-10 mm, for example, it can be 3 mm, 4 mm, 5.0 mm, 6.0 mm, 7.0 mm, 8.0 mm, 9.0 mm or 10.0 mm, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0021] Preferably, the current collector selected in step 2 can be aluminum foil, porous aluminum foil, carbon-coated aluminum foil, gold foil, porous gold foil, titanium foil or titanium mesh, preferably aluminum foil.
[0022] Preferably, the width of the rectangular current collector selected in step 2 is smaller than the aperture of the polytetrafluoroethylene mold, and the length of the rectangular current collector selected is greater than the height of the injected slurry.
[0023] Preferably, the standing time selected in step 2 includes 6-24 hours, for example, it can be 6 hours, 12 hours, 18 hours or 24 hours, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0024] Preferably, the heating temperature selected in step 2 includes 60-120°C, for example, it can be 60°C, 70°C, 80°C, 90°C, 100°C, 110°C or 120°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0025] Preferably, the heating time selected in step 2 includes 12-24 hours, for example, it can be 12 hours, 14 hours, 16 hours, 18 hours, 20 hours or 24 hours, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0026] Preferably, the membrane material selected in step three can be a porous polymer membrane, a non-woven membrane, an inorganic composite membrane, a polyolefin membrane, a polyimide membrane, a polyamide membrane or a spandex or aramid membrane, preferably a polyolefin membrane.
[0027] As a preferred technical solution of the preparation method described in the first aspect of the present invention, the preparation method comprises:
[0028] Step 1: Place a carbon fluoride raw material with a fluorine-carbon ratio of 0.5-1.3, a conductive agent and a binder in a ball mill at a ratio of 95:3:2, 90:5:5, 80:10:10 or 75:15:10, then inject 50-300 μL of solvent into the ball mill, and then place corresponding zirconia ball milling beads at a ball-to-material ratio of 6:1, 8:1, 12:1, 16:1, or 20:1, and ball mill at a speed of 300-1200 r / min for 2-12 hours to obtain a battery positive electrode slurry.
[0029] Step 2: Inject the positive electrode slurry obtained in step 1 into a polytetrafluoroethylene mold with a pore size of 3-10 mm, then embed a rectangular aluminum foil, porous aluminum foil, carbon-coated aluminum foil, gold foil, porous gold foil, titanium foil or titanium mesh current collector into the positive electrode slurry, let it stand at room temperature for 6-24 hours, then transfer it to a vacuum oven, heat it at 60-120°C for 12-24 hours until the solvent is completely evaporated, and finally obtain a cylindrical positive electrode.
[0030] Step 3: Wrap the separator material and the negative electrode lithium ribbon in sequence on the surface of the cylindrical positive electrode obtained in step 2 to form a cylindrical non-wound battery cell.
[0031] In a second aspect, the present invention provides a cylindrical non-wound battery cell, wherein the cylindrical non-wound battery cell is obtained by the preparation method described in the first aspect.
[0032] Preferably, the cylindrical non-wound battery core has a diameter of 4-12 mm and a height of 5-20 mm.
[0033] Preferably, the cylindrical non-wound battery cell is used in a primary battery.
[0034] Preferably, the cylindrical non-wound battery cell has the advantages of high energy density, good structural stability and high safety.
[0035] The numerical range described in the present invention not only includes the point values listed above, but also includes any point values between the above numerical ranges that are not listed. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0036] Compared with the prior art, the present invention has the following advantages:
[0037] 1. The non-wound battery cell prepared by the present invention can more effectively utilize the internal space of the battery, reduce the gap, and thus improve the energy density of the battery, which is of great significance for improving the service life and performance of microelectronic devices.
[0038] 2. The structure of the non-wound battery cell prepared by the present invention helps to reduce the uneven distribution of internal stress, reduce the risk of pole piece breakage and material dropout, and thus improve the safety of the battery.
[0039] 3. The cylindrical non-wound battery cell structure prepared by the present invention improves the heat dissipation efficiency of the battery and enhances the reliability of the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] Figure 1 Schematic diagram of the cross-section structure of a cylindrical non-wound battery cell
[0041] Figure 2 Schematic diagram of the top of a cylindrical non-wound battery cell
[0042] Figure 3 SEM image of fluorinated graphene positive electrode
[0043] Figure 4 SEM image of fluorinated hard carbon cathode
[0044] Figure 5 Constant current discharge curve of cylindrical non-wound battery cell using fluorinated graphene positive electrode
[0045] Figure 6 Constant current discharge curve of cylindrical non-wound battery cell using fluorinated hard carbon positive electrode
[0046] Description of Figure Numbers:
[0047] Among them, 1-current collector; 2-cylindrical positive electrode; 3-separator; 4-negative electrode. DETAILED DESCRIPTION
[0048] The present invention is described in detail below with reference to the accompanying drawings and embodiments:
[0049] Example 1
[0050] Step 1: Place the fluorinated graphene raw material with a fluorine-carbon ratio of 1.0, Ketjen black and polyvinylidene fluoride in a ball mill at a ratio of 80:10:10, then inject 150 μL of N-methylpyrrolidone into the ball mill, and then place the corresponding zirconium oxide ball milling beads at a ball-to-material ratio of 20:1, and ball mill at a speed of 500 r / min for 6 hours to obtain the battery positive electrode slurry.
[0051] Step 2: Inject the positive electrode slurry obtained in step 1 into a polytetrafluoroethylene mold with a pore size of 4 mm, then embed the rectangular aluminum foil current collector into the positive electrode slurry, let it stand at room temperature for 12 hours, then transfer it to a vacuum oven, heat it at 120°C for 24 hours until the solvent is completely evaporated, and finally obtain a cylindrical positive electrode.
[0052] Step 3: Wrap the separator material and the negative electrode lithium ribbon in sequence on the surface of the cylindrical positive electrode obtained in step 2 to form a cylindrical non-wound battery cell.
[0053] As attached Figure 1-2 As shown, the cylindrical non-wound battery cell includes a current collector 1, a cylindrical positive electrode 2, a separator 3 and a negative electrode 4, the current collector 1 is embedded in the middle of the cylindrical positive electrode 2, the width of the current collector 1 is smaller than the diameter of the cylindrical positive electrode 2, the length of the current collector 1 is greater than the height of the cylindrical positive electrode 2, the separator 3 is wrapped on the surface of the cylindrical positive electrode 2, and the negative electrode 4 is wrapped on the surface of the separator 3.
[0054] As attached Figure 3 As shown in the scanning electron microscope image of the fluorinated graphene positive electrode, the selected fluorinated graphene has a flake structure with a thickness of only a few nanometers and obvious wrinkles on the surface.
[0055] The cylindrical non-wound cells prepared in Example 1 were assembled into cylindrical batteries and the electrochemical performance was tested. Figure 5 As shown, at a current density of 0.05C, the cylindrical non-wound battery cell exhibited a high discharge specific capacity of 830 mAh / g, close to 96% of the theoretical capacity (865 mAh / g).
[0056] Example 2
[0057] Step 1: Place the fluorinated graphene raw material with a fluorine-carbon ratio of 1.0, Ketjen black and polytetrafluoroethylene in a ball mill at a ratio of 80:10:10, then inject 50 μL of water into the ball mill, and then place the corresponding zirconia ball milling beads at a ball-to-material ratio of 20:1, and ball mill at a speed of 600 r / min for 6 hours to obtain the battery positive electrode slurry.
[0058] Step 2: Inject the positive electrode slurry obtained in step 1 into a polytetrafluoroethylene mold with a pore size of 4 mm, then embed the rectangular aluminum foil current collector into the positive electrode slurry, let it stand at room temperature for 12 hours, then transfer it to a vacuum oven, heat it at 120°C for 24 hours until the solvent is completely evaporated, and finally obtain a cylindrical positive electrode.
[0059] Step 3: Wrap the separator material and the negative electrode lithium ribbon in sequence on the surface of the cylindrical positive electrode obtained in step 2 to form a cylindrical non-wound battery cell.
[0060] Example 3
[0061] Based on Example 2, the positive electrode material is fluorinated hard carbon, and other components and preparation process are consistent with Example 2.
[0062] As attached Figure 4 As shown in the scanning electron microscope image of the positive electrode material fluorinated hard carbon, the selected fluorinated hard carbon is irregular block particles with uneven sizes.
[0063] Example 4
[0064] Step 1: Place the fluorinated hard carbon raw material with a fluorine-carbon ratio of 1.1, Ketjen black and polytetrafluoroethylene in a ball mill at a ratio of 90:5:5, then inject 100 μL of water into the ball mill, and then place the corresponding zirconium oxide ball milling beads at a ball-to-material ratio of 20:1, and ball mill at a speed of 500 r / min for 6 hours to obtain the battery positive electrode slurry.
[0065] Step 2: Inject the positive electrode slurry obtained in step 1 into a polytetrafluoroethylene mold with a pore size of 4 mm, then embed the rectangular aluminum foil current collector into the positive electrode slurry, let it stand at room temperature for 12 hours, then transfer it to a vacuum oven, heat it at 120°C for 24 hours until the solvent is completely evaporated, and finally obtain a cylindrical positive electrode.
[0066] Step 3: Wrap the separator material and the negative electrode lithium ribbon in sequence on the surface of the cylindrical positive electrode obtained in step 2 to form a cylindrical non-wound battery cell.
[0067] The cylindrical non-wound cells prepared in Example 4 were assembled into cylindrical batteries and the electrochemical performance was tested. Figure 6As shown, at a current density of 0.05C, the cylindrical non-wound battery cell exhibited a high discharge specific capacity of 764 mAh / g, close to 88.3% of the theoretical capacity (865 mAh / g).
[0068] The preferred embodiments of the present invention have been specifically described above, but the present invention is not limited to the embodiments. Those skilled in the art may make various equivalent modifications or substitutions without violating the spirit of the present invention. These equivalent modifications or substitutions are all included in the scope defined by the claims of this application.
Claims
1. A method for preparing a cylindrical non-wound battery cell, characterized in that: The preparation method is prepared according to the following steps: Step 1: Place the fluorinated carbon raw materials with different fluorine-carbon ratios, the conductive agent and the binder in a ball mill according to a certain ratio, then inject an appropriate amount of solvent into the ball mill, and then place the corresponding ball mill beads according to a certain ball-to-material ratio, and ball mill at a certain speed for a period of time to obtain the positive electrode slurry of the battery; Step 2: inject the positive electrode slurry obtained in step 1 into a polytetrafluoroethylene mold with a certain pore size, then embed the rectangular current collector into the positive electrode slurry, let it stand for a period of time at room temperature, then transfer it to a vacuum oven, heat it at a set temperature for a period of time until the solvent is completely evaporated, and finally obtain a cylindrical positive electrode; Step 3: Wrap the separator material and the negative electrode lithium ribbon in sequence on the surface of the cylindrical positive electrode obtained in step 2 to form a cylindrical non-wound battery cell.
2. The preparation method according to claim 1, characterized in that: The fluorine-carbon ratio of the fluorinated carbon material selected in step 1 is 0.5-1.3, for example, it can be 0.5, 0.6, 0.8, 1.0, 1.1 or 1.3, but is not limited to the listed values, and other values not listed within the numerical range are also applicable; Preferably, the fluorinated carbon selected in step 1 includes any one of fluorinated hard carbon, fluorinated graphite, fluorinated graphene, fluorinated carbon nanotubes, fluorinated carbon fibers, fluorinated carbon quantum dots, fluorinated redox graphene, fluorinated carbon microspheres, and fluorinated asphalt, or a combination of at least two thereof, preferably fluorinated graphite; Preferably, the conductive agent selected in step 1 includes any one of Ketjen black, acetylene black, graphite, activated carbon, carbon nanotubes, and Super P, or a combination of at least two thereof, preferably Ketjen black; Preferably, the binder selected in step 1 includes any one of polyvinylidene fluoride, sodium carboxymethyl cellulose, styrene-butadiene rubber, polytetrafluoroethylene, polyacrylic acid, and polyvinyl alcohol, or a combination of at least two thereof, preferably polyvinylidene fluoride; Preferably, the ratio of the fluorinated carbon material to the conductive agent and the binder selected in step 1 can be 95:3:2, 90:5:5, 80:10:10 or 75:15:10, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
3. The preparation method according to claim 1-2, characterized in that: The solvent selected in step 1 can be any one of water, ethanol, methanol, isopropanol, N,N-dimethylformamide, acetonitrile, dimethyl sulfoxide or N-methylpyrrolidone, or a combination of at least two thereof, preferably N-methylpyrrolidone; Preferably, the amount of solvent selected in step 1 is 50-300 μL, for example, 50 μL, 100 μL, 150 μL, 200 μL, 250 μL or 300 μL, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
4. The preparation method according to any one of claims 1 to 3, characterized in that The ball-to-material ratio selected in step 1 is 6-20, for example, 6:1, 8:1, 12:1, 16:1, or 20:1, but is not limited to the listed values, and other values not listed within the numerical range are also applicable; Preferably, the ball milling speed selected in step 1 is 300-1200 r / min, for example, 300 r / min, 500 r / min, 800 r / min, 1000 r / min or 1200 r / min, but is not limited to the listed values, and other values not listed in the numerical range are also applicable; Preferably, the ball milling time selected in step 1 is 2-12 h, for example, 2 h, 4 h, 6 h, 8 h, 10 h or 12 h, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
5. The preparation method according to any one of claims 1 to 4, characterized in that: The aperture size of the polytetrafluoroethylene mold selected in step 2 is 3-10 mm, for example, it can be 3 mm, 4 mm, 5.0 mm 6.0 mm, 7.0 mm, 8.0 mm, 9.0 mm, or 10.0 mm, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
6. The preparation method according to any one of claims 1 to 5, characterized in that: The current collector selected in step 2 can be aluminum foil, porous aluminum foil, carbon-coated aluminum foil, gold foil, porous gold foil, titanium foil or titanium mesh, preferably aluminum foil; Preferably, the width of the rectangular current collector selected in step 2 is smaller than the aperture of the polytetrafluoroethylene mold, and the length of the rectangular current collector selected is greater than the height of the injected slurry.
7. The preparation method according to any one of claims 1 to 6, characterized in that: The standing time selected in step 2 includes 6-24 hours, for example, 6 hours, 12 hours, 18 hours or 24 hours, but is not limited to the listed values, and other values not listed within the numerical range are also applicable; Preferably, the heating temperature selected in step 2 includes 60-120°C, for example, 60°C, 70°C, 80°C, 90°C, 100°C, 110°C or 120°C, but is not limited to the listed values, and other values not listed within the numerical range are also applicable; Preferably, the heating time selected in step 2 includes 12-24 hours, for example, it can be 12 hours, 14 hours, 16 hours, 18 hours, 20 hours or 24 hours, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
8. The preparation method according to any one of claims 1 to 7, characterized in that: The membrane material selected in step three can be a porous polymer membrane, a non-woven membrane, an inorganic composite membrane, a polyolefin membrane, a polyimide membrane, a polyamide membrane or a spandex or aramid membrane, preferably a polyolefin membrane.
9. The preparation method according to any one of claims 1 to 8, characterized in that: The preparation method comprises: Step 1: placing a fluorinated carbon raw material with a fluorine-carbon ratio of 0.5-1.3, a conductive agent and a binder in a ratio of 95:3:2, 90:5:5, 80:10:10 or 75:15:10 in a ball mill, then injecting 50-300 μL of a solvent into the ball mill, and then placing corresponding zirconium oxide ball milling beads at a ball-to-material ratio of 6:1, 8:1, 12:1, 16:1, or 20:1, and ball milling at a speed of 300-1200 r / min for 2-12 hours to obtain a battery positive electrode slurry; Step 2: Inject the positive electrode slurry obtained in step 1 into a polytetrafluoroethylene mold with a pore size of 3-10 mm, then embed a rectangular aluminum foil, porous aluminum foil, carbon-coated aluminum foil, gold foil, porous gold foil, titanium foil or titanium mesh current collector into the positive electrode slurry, let it stand at room temperature for 6-24 hours, then transfer it to a vacuum oven, heat it at 60-120°C for 12-24 hours until the solvent is completely evaporated, and finally obtain a cylindrical positive electrode; Step 3: Wrap the separator material and the negative electrode lithium ribbon in sequence on the surface of the cylindrical positive electrode obtained in step 2 to form a cylindrical non-wound battery cell.
10. A cylindrical non-wound battery cell, characterized in that: The cylindrical non-wound battery cell is obtained by the preparation method according to any one of claims 1 to 9; Preferably, the cylindrical non-wound battery core has a diameter of 4-12 mm and a height of 5-20 mm; Preferably, the cylindrical non-wound battery cell is used for a primary battery; Preferably, the cylindrical non-wound battery cell has the advantages of high energy density, good structural stability and high safety.